2007
DOI: 10.1617/s11527-007-9267-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the aggregate quality on the physical properties of natural feebly-hydraulic lime mortars

Abstract: This paper examines the influence of the shape, average size and calcite content of the aggregate on strength, porosity, water absorption, density and capillary suction of natural feeblyhydraulic lime (NHL 2) mortars. Four types of aggregate were analysed in order to determine calcite content, particle shape and average particle size. Four different mortar mixes were then designed and produced using each of the aggregate types and NHL 2 as a binder. The mixing and curing as well as the aggregate:binder proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 3 publications
2
25
1
Order By: Relevance
“…The compressive strengths recorded are comparable to those reported by previous authors [7,12,21]. In addition, the values obtained compare well to those of equivalent 1:3, NHL2 mortars previously studied [22,23]. This suggests that Mg-lime develops strength similarly to feeblyhydraulic lime, reaching comparable ultimate values as regards resistance to compression.…”
Section: Compressive Strengthsupporting
confidence: 89%
See 1 more Smart Citation
“…The compressive strengths recorded are comparable to those reported by previous authors [7,12,21]. In addition, the values obtained compare well to those of equivalent 1:3, NHL2 mortars previously studied [22,23]. This suggests that Mg-lime develops strength similarly to feeblyhydraulic lime, reaching comparable ultimate values as regards resistance to compression.…”
Section: Compressive Strengthsupporting
confidence: 89%
“…8 and [22,23]), however, the strength development may be slightly slower than that of NHL2. According to the results obtained, the 100% Mg-lime mortar is 1.75 times stronger in flexion than the CL mortar, and, roughly, the greater the amount of Mg-lime in the mix, the greater the flexural strength.…”
Section: Flexural Strengthmentioning
confidence: 93%
“…As it has been reported (Lanas et al 2006;Pavia and Toomey 2008) there is a close relation between the pore structure, the mechanical properties and the water absorption of mortars. By adding aggregate these properties can be modified.…”
Section: Discussionsupporting
confidence: 63%
“…However, Holmes and Windgate (3) disagree, claiming that limestone aggregate produces weaker lime mortars. Pavía and Toomey (4) found that natural hydraulic lime mortars (NHL2) with limestone aggregate were slightly weaker than those with sandstone and quartz aggregate. Some of these discrepancies are due to the use of different 'parent' limestones to produce the aggregate and different lime binders.…”
Section: Influence Of Aggregate In Lime Mortarsmentioning
confidence: 99%